Minuman Keras dalam Masyarakat Batavia - Andana, Muhammad Lingga; Damayanti, Silviyana; Miftahuddin, Miftahuddin (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This article reviews the book Minuman Keras di Batavia Akhir Abad XIX (Alcoholic Beverages in Batavia in the Late 19th Century) by Yusana Sasanti Dadtun, which examines the socio-economic history of alcoholic beverages in Batavia at the end of the 19th century. Originally a master's thesis at Gadjah Mada University, this book explores the production, trade, and regulation of alcoholic beverages amid the social dynamics of colonial society. The method used in this review is descriptive-analytical, highlighting how alcoholic beverages were not only an important economic commodity but also a symbol of social status. This article dissects the cultural shifts in alcohol consumption in Batavia, including the role of the native elite in adopting Western lifestyles, as well as its impact on local social and economic structures. Through this study, it is shown that alcoholic beverages played a role in shaping social stratification and the modernization of consumption culture in the colonial era.